2021
DOI: 10.3390/molecules26247568
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Degradation Product Formation during Biodegradation of Expanded Polystyrene by Mealworm Larvae under Different Feeding Strategies

Abstract: Polystyrene (PS) is a plastic polymer extensively used for food packaging. PS is difficult to decompose and has low recycling rates, resulting in its accumulation in the environment, in the form of microplastic particles causing pollution and harming oceans and wildlife. Degradation of PS by mealworms (Tenebrio molitor) has been suggested as a possible biological strategy for plastic contamination; however, the biodegradation mechanism of PS by mealworms is poorly understood. It is hypothesized that the gut mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…These findings suggest that the bran can enhance the PBAT consumption by mealworms, but only a mixture feedstock with a low PBAT addition percentage (e.g., 10–20% PBAT) is suitable for rapid PBAT ingestion and recycling. This could be because the biodegradation of the PBAT mixture feedstock with high PBAT contents could not provide efficient energy and elements for the digestive enzymes of mealworms. , On the other hand, the SPCRs by mealworms in this study (12.9 to 37.8 mg PBAT 100 larvae –1 d –1 , Tables S4 and S6) were remarkably lower than the specific consumption rates of PLA microplastics (45.2 to 202.7 mg PLA 100 larvae –1 d –1 ) but comparable to the specific consumption rates of nonbiodegradable plastic materials (e.g., PVC microplastics, PS and LDPE foams, ,,, and PP foam , ). These findings suggest that mealworms may not have the same affinity for all degradable plastics (e.g., PHA, PCL, PLA, PBAT, etc.).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…These findings suggest that the bran can enhance the PBAT consumption by mealworms, but only a mixture feedstock with a low PBAT addition percentage (e.g., 10–20% PBAT) is suitable for rapid PBAT ingestion and recycling. This could be because the biodegradation of the PBAT mixture feedstock with high PBAT contents could not provide efficient energy and elements for the digestive enzymes of mealworms. , On the other hand, the SPCRs by mealworms in this study (12.9 to 37.8 mg PBAT 100 larvae –1 d –1 , Tables S4 and S6) were remarkably lower than the specific consumption rates of PLA microplastics (45.2 to 202.7 mg PLA 100 larvae –1 d –1 ) but comparable to the specific consumption rates of nonbiodegradable plastic materials (e.g., PVC microplastics, PS and LDPE foams, ,,, and PP foam , ). These findings suggest that mealworms may not have the same affinity for all degradable plastics (e.g., PHA, PCL, PLA, PBAT, etc.).…”
Section: Resultsmentioning
confidence: 61%
“…On the other hand, the C e value was limited (∼3%) in all frass samples (Figure a), which were 1.9 ± 0.2, 2.0 ± 0.0, 2.3 ± 0.1, 2.4 ± 0.1, 2.6 ± 0.0, 2.8 ± 0.1, and 3.1 ± 0.2% for the mealworms fed on bran, PBAT–bran mixture (the PBAT content of 10, 20, 40, 60, and 80%), and 100% PBAT diets, respectively (Table S7), suggesting that more lipophilic products were produced by PBAT digestion and biodegradation. , In this research, we did not analyze the polar and nonpolar degradation compounds in the frass residue derived from the PBAT-fed mealworms via GC-metabolomics. Tsochatzis et al identified fatty acids, amides, long-chain hydrocarbons, and a relatively low total amount of styrene and PS oligomers (dimers, trimers) in the intestine tissue and frass of mealworms after PS biodegradation by metabolic profiling. ,, The PBAT polymer belongs to the aromatic–aliphatic co-polyester family and contains benzene rings and ester bonds within its polymer structure, which might be depolymerized and degraded into similar degradation substances and intermediates. Follow-up research focusing on the metabolome should help determine the degradation products derived from polymers via GC-metabolomics and other technical methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the experiment (17 days) in addition to Lactococcus, Pediococcus and Enterococcus different bacteria could be also associated to PU diet (Figure 8). Bacteria such as Paraclostridium (Firmicutes) or Chryseobacterium (Bacteroidetes) this last already observed in mealworm gut on different PS diets [53] and Kosakonia and Pseudomonas (Proteobacteria). Kosakonia member of Enterobacteriaceae, a family known to contain PE degrading bacteria (Enterobacter asburiae YT1) [54] that can use oxygen for biodegradation, already observed in PE and PS degradation [55,56].…”
Section: Microbial Community Of Mealworm Gutmentioning
confidence: 71%
“…At the end of the experiment (17 days), in addition to Lactococcus , Pediococcus, and Enterococcus, different bacteria could also be associated with the PU diet ( Figure 8 ) such as Paraclostridium (Firmicutes), Chryseobacterium (Bacteroidetes), Kosakonia , and Pseudomonas (Proteobacteria). Chryseobacterium was observed in the mealworm gut with the different PS diets [ 52 ]. Kosakonia, a member of the Enterobacteriaceae family has been observed in PE and PS degradation [ 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%